Current trends in plastic reconstructive surgery of urogenital area - N. O. Milanov; R. T. Adamyan; O. I. Startseva; A. L. Istranov (Сеченовский вестник, 2014)
The paper analyzes the current approaches to the study of plastic reconstructive surgery of the urogenital area.